Transient response and frequency domain analysis of an electrically variable transmission - Enrico Galvagno; Alessandro Vigliani; Mauro Velardocchia (Advances in Mechanical Engineering, 2018)
This article deals with the dynamic behavior of a passenger car equipped with an electrically variable transmission, which is analyzed both in time and frequency domains. After deriving the dynamic equations in the state-space form for both open- and closed-loop systems, a methodology for objectively evaluating the drivability of this over-actuated system is proposed. Several simulation results are presented with the aim of highlighting the transient response to fast engine torque changes and the effect of the generator speed controller calibration on the system dynamics. Moreover, the influence of the ratio between electrical and thermal power on the frequency response is discussed. The proposed analysis, which is based on a simple static torque split between internal combustion engine and propulsion electric motor, depicts the dynamic signature of the electrically variable transmission powertrain system, without any additional drivability filter. Hence, these results can constitute the base for the design of dynamic torque splitting aimed at optimizing the longitudinal vehicle response to the driver’s acceleration demand.